The band energy structure of RbKSO₄ crystals - Bovgyra, O.V.; Stadnyk, V.Yo.; Franiv, A.V.; Tuzyak, M.R.; Chyzh, O.Z. (Condensed Matter Physics, 2007)
The energy band structure of mechanically free and compressed RbKSO₄ single crystals is investigated. It is established that the top of the valence band is located at the D point of the Brillouin zone [k = (0.5, 0.5, 0)], the bottom of the conduction band lies at the Γ point, and the minimum direct band gap Eg is equal to 5.80 eV. The bottom of the conduction band is predominantly formed by the K s, Li p, Rb s, and Rb p states hybridized with the S p and O p antibonding states. The pressure coefficients of the energy position of the valence and conduction band states and the band gap Eg are determined.